Consumer demand and willingness to pay for safe food in Accra, Ghana: Implications for public and private sectors’ roles in food safety management - Ragasa, Catherine; Andam, Kwaw S.; Amewu, Sena; Asante, Seth (International Food Policy Research Institute, 2019)
Consumer demand for food safety is likely to be an important driver of public policies and industry-led efforts to reduce information asymmetry on food attributes and improved food safety. This paper examines the attribute demand for chicken meat and tilapia among 803 shoppers in Accra, Ghana. Freshness is the main attribute demanded by the overwhelming majority of shoppers, followed by food safety, price, taste and size. Consumers are willing to pay price premiums for food safety certifications, i.e., those certified according to Hazard Analysis and Critical Control Point (HACCP) principles or certified as free of antibiotic residue. However, the price premium shoppers are willing to pay for improved food safety vary by shoppers type. A third of tilapia shoppers and half of chicken meat shoppers are classified as food safety conscious shoppers and willing to pay a 10 to 12 percent higher price than noncertified products. In comparison, only a tenth of shoppers are considered to be price conscious and willing to pay a small premium (< 1 percent) for certified safe foods. We also tested an information treatment on the negative health implications of food contamination and its effect on shoppers’ decisions. The information treatment randomly assigned to shoppers was a significant predictor of food safety attribute demand for chicken meat but not for tilapia, which may be linked to greater awareness of and concern about antibiotic misuse in poultry production. Our findings generally point to a concern about food safety and a strong demand and willingness among consumers to pay premiums for certified safe foods, thus providing support for public- or industry-led schemes to provide food safety information to consumers.